A Practical Study of LEED Certification for the Shanghai Tower Building Project - Zhang, Bin (International Journal of Global Economics and Management, 2024)
This paper examines the effective application of LEED certification in the Shanghai Centre Towers project, analysing its green building practices in all phases of design, construction and operation. By delving into key areas such as energy efficiency, renewable energy use, water management and material selection, it reveals how LEED certification promotes sustainable building development. The results of the study show that Shanghai Centre Tower has not only successfully obtained LEED Gold certification, but also become a benchmark for green buildings, providing valuable experience and reference for future commercial projects.